Analysis of Tense Selection in Heavenâ€™s Song Lyric by Calum Scott and Lyodra Ginting - Feranty, Livia; Amalia, Resti; Bowo, Tri Arie (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2023)
This study aims to determine the type of tense used in the lyrics of the song â€œHeavenâ€ by Lyodra Ginting and Calum Scott. The research method used in this study is a qualitative descriptive research method. The data used in this study came from the lyrics of the song â€œHeaven,â€ which Calum Scott wrote and sang by himself and Lyodra Ginting. The researcher uses the theory of grammar and style in Stylistics to analyze the tenses selection in the song lyrics data. The study results show that this songâ€™s lyrics predominantly use the simple present tense, and the rest use the present continuous tense, present perfect continuous tense, simple past tense, past continuous tense, and past future tense. There are reasons behind the songwriterâ€™s tense selection. The tense in the song is dominated by simple present tense to express a habitual use indicating a generalization over a set of times. Keywords: Calum Scott; Heaven; Lyodra Ginting; Stylistics; Tense Selection; Song Lyrics